2023
DOI: 10.1002/anie.202301563
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol‐Induced Strong Metal‐Support Interactions in a Supported Copper/ZnO Catalyst

Abstract: Tuning the strong metal‐support interaction (SMSI) in metal catalysts is a promising strategy to improve their catalytic performance. In this article, we systematically investigated the influences of different alcohol/water mixtures on the evolution of the interfacial structure of Cu/ZnO catalysts in the reduction stage. A series of in situ characterization and theoretical simulation studies were performed to elucidate the various mechanisms of alcohol induced SMSI. It was found that when methanol/water is add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…The quest for a comprehensive understanding of SMSIs entails delving into their chemical nature and catalytic mechanisms, a long-standing challenge in the field. Cutting-edge in situ / operando characterization techniques, including electron microscopy (e.g., HRTEM, STEM, ETEM) and spectroscopy techniques (e.g., XPS, UPS, EXAFS, XRD, FT-IR, HS-LEIS, EPR, Raman) and temperature-programmed desorption and reduction experiments, combined with DFT calculations, have been utilized to decipher the chemical nature and the underlying catalytic mechanisms of SMSIs. ,, For example, the extent and direction of electron transfer can be identified via in situ X-ray photoelectron spectroscopy (XPS) and in situ X-ray absorption near-edge structure spectroscopy, coupled with in situ CO-DRIFTS. , The alteration of the metal d band center has been investigated using ultraviolet photoelectron spectroscopy (UPS) combined with DFT calculations, revealing substantial electronic perturbations at the interface. , …”
Section: Unveiling the Chemical Nature Of Smsis Via Advanced Characte...mentioning
confidence: 99%
“…The quest for a comprehensive understanding of SMSIs entails delving into their chemical nature and catalytic mechanisms, a long-standing challenge in the field. Cutting-edge in situ / operando characterization techniques, including electron microscopy (e.g., HRTEM, STEM, ETEM) and spectroscopy techniques (e.g., XPS, UPS, EXAFS, XRD, FT-IR, HS-LEIS, EPR, Raman) and temperature-programmed desorption and reduction experiments, combined with DFT calculations, have been utilized to decipher the chemical nature and the underlying catalytic mechanisms of SMSIs. ,, For example, the extent and direction of electron transfer can be identified via in situ X-ray photoelectron spectroscopy (XPS) and in situ X-ray absorption near-edge structure spectroscopy, coupled with in situ CO-DRIFTS. , The alteration of the metal d band center has been investigated using ultraviolet photoelectron spectroscopy (UPS) combined with DFT calculations, revealing substantial electronic perturbations at the interface. , …”
Section: Unveiling the Chemical Nature Of Smsis Via Advanced Characte...mentioning
confidence: 99%
“… [129,130] The degree of coverage affects the reactivity for CO oxidation. Recent theoretical and experimental studies demonstrate that alcohols show high the reducing potential and, hence, potentially promote the reduction of oxide supports [131] …”
Section: Effect Of Gas Environment On Metal‐support Interactionsmentioning
confidence: 99%
“…found that exposing the commercial Cu/ZnO/Al 2 O 3 catalyst to an H 2 /H 2 O/CH 3 OH/N 2 mixture at 300 °C and atmospheric pressure is found to accelerate the migration of ZnO x species onto the surface of metallic Cu 0 nanoparticles via an adsorbate‐induced SMSI. Studies, both theoretical and experimental, show that adding methanol/water is added to H 2 during the reduction pretreatment, more oxygen vacancies are formed on the ZnO support, which facilitates the dissociation of H 2 O and the hydroxylation of ZnO species [131] . Zhang et al [141] .…”
Section: Effect Of Gas Environment On Metal‐support Interactionsmentioning
confidence: 99%
“…Three infrared bands at 2130, 2103−2104, and 2085−5086 cm −1 are assigned to CO adsorption on large Cu NPs, Cu + , and metallic Cu 0 sites, respectively. 30,42 The Cu + species are generally believed to originate from the Cu−ZnO interface. 42,43 The Cu + /(Cu 0 + Cu + ) ratio is 80.7% for CZAM-250Ar-R and 71.1% for CZM-250Ar-R, which is consistent with the XPS results.…”
Section: Synthesis Of Copper Mesh Catalysts and Activitiesmentioning
confidence: 99%
“…30,42 The Cu + species are generally believed to originate from the Cu−ZnO interface. 42,43 The Cu + /(Cu 0 + Cu + ) ratio is 80.7% for CZAM-250Ar-R and 71.1% for CZM-250Ar-R, which is consistent with the XPS results.…”
Section: Synthesis Of Copper Mesh Catalysts and Activitiesmentioning
confidence: 99%